KONSEP NEURO PARENTING DAN IMPLEMENTASINYA DALAM PEMBENTUKAN KARAKTER ANAK - indriyani, rahmawati; Haryanto, Sri; Rizqi, Sofan (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2023)
This study aims to determine the concept of nauro parenting, to determine children's character based on brain performance, and to determine obstacles in the formation of children's character based on brain performance. This study uses a type of library research (library research). The bibliographical method is a type of qualitative research method where the location and place of research is carried out in libraries, documents, archives, and the like. Neuro parenting according to Zuhdi in Neuro Leadership Indonesia says that parenting neuroscience or neuro parenting is a term created to describe everything related to brain performance-based parenting. It is stated that the main purpose of parenting is to form one's noble behavior (character). To form noble behavior requires good thinking/feeling. And this process occurs at the level of neurons (brain nerve cells). It turns out that the process of thinking and behaving in humans, including the nurturing process, occurs at the level of neurons (brain nerve cells). Therefore, in general, neuro-parenting is defined as the science of brain performance-based parenting